A Historical Survey on the Church’s Involvement in Peace Initiative Frameworks in Zimbabwe: Post-Mugabe Era - Musoni, Phillip; Masondo, Sibusiso (Studia historiae ecclesiasticae, 2024)
The article highlights that numerous peace initiative programmes have been implemented by both the government and the Church to promote reconciliation, healing, and social unity within Zimbabwe's politically charged atmosphere. Despite these efforts, political violence continued to surge during and post-Mugabe era. Furthermore, the study interrogates the role of the church in the peace initiative frameworks after the Mugabe era. Historically, the church's involvement in peace initiatives has been minimal, comparable to a mere drop in the ocean. The study posits that the Zimbabwean church could enhance its role in peace initiatives within a politically fragmented context by reinforcing to its congregants the significance of embodying the spirituality of Jesus Christ alongside African spirituality, thereby cultivating what this article refers to as 'African Christian spirituality'. The study observed that the majority of churches in Zimbabwe have not integrated African Christian spirituality into their peace initiative programmes. A spirituality with tenets such as love, tolerance, forgiveness, hunhu, respect for human life, and unity in diversity among others serves as a foundation for peace in a politically divided nation like Zimbabwe.  A review of the literature, participant observation and interviews were used for data collection. Theological reflection and socio-historical approaches were employed to interpret the data collected.